SISTEM AUGMENTED REALITY (AR) DALAM DAKWAH ISLAM - Mochamad T. A. Aziz Zein; Ninik Agustin (Institut Agama Islam Imam Ghozali, 2020)
The Use Of Mobile Technology In The Industrial 4.0 Era Is A Must. The Number Of Smartphone Users Continues To Increase Over Time. Contiinum Reality Technology Which Consists Of Both Virtual Reality (VR) And Augmented Reality (AR) Becomes A Portable Technology That Is Easy And Affordable Being Used With A Smartphone. This Study Has An Objective To Determine The Potential Uses Of Augmented Reality (AR) Technology In Modern Islamic Da'wa. This Study Are Counted As A Literature Study Using The Traditional Review Method.AR Applications Have Been Used In Many Fields, Such As Medical, Military, Manufacturing, Visualization, Entertainment And Games, Robotics, Education, Marketing, Navigation, Tourism, Geospatial, Urban Planning And Civil Sciences. Da’wa Requires Attention In Both Truth And Good Ability Of The Preachers. It’s Based On Legal Aspects And The Procedures (Fiqhud-Dakwah). There Was Limited Amount Of Research And AR Products Used In Da'wa. The AR’s Technology That Can Be Applied In Islamic Da'wa Are 1) Playing Cards For Da’wa, 2) Islamic Story Books, 3) Da’wa Brochures / Leaflets / Poster, 4) Islamic History Museum.